Vtelená kognícia, jej filozofické východiská a potenciálny význam pre pedagogiku. / Embodied cognition, its philosophical basis and its potential relevance for educational sciences. - Zuzana Obertová (Czech Pedagogical Society, 2013)
The purpose of this paper is to describe the theory of embodied cognition, embed it in broader philosophical framework, and induct its potential contribution to educational sciences. Text progresses from clarifying the concept of embodiment, its origins in phenomenology (M. Merleau-Ponty) and use in cultural anthropology (T. J. Csordas). In the next section, we elaborate on the philosophical framework which had an impact on the theory of embodied cognition and suppression of the dualistic view of mind and body; we clarify aspects of embodiment complementing the image ofembodiment. As part of the description of the contribution of the embodied cognition to educational sciences we focus on two areas: language and mathematics, which are considered to be largely cognitive and abstract concepts separate from the body. Ithas been shown that the theory of embodied cognition does not sufficiently explain what the body actually is, and what kind of body is discussed here. It follows from this that in both of the areas (language and mathematics) a particularly importantaspect for the process of understanding abstract systems and learning is the research on and the importance of gestures and physical experience. We found that the asset of embodied cognition for educational sciences lies in the orientation towardbodily action, activity and impact of physical environment and bodily experience on cognition, which facilitate the learning process.